2008
DOI: 10.1016/j.ijgo.2008.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the use of epidural analgesia in Australia

Abstract: Changes in maternal or birth characteristics partially explain the increase in epidural analgesia rate. The unexplained increase may be due to increased availability or other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…A US-based study found similar, but not statistically significant, higher odds of epidural use associated with induction of labor (OR = 2.30, 95% CI 0.50 - 9.40) [9]. Further, an Australian study reported higher odds of epidural use among women with induced labor, similar to our report (OR = 1.86, 95% CI 1.83 - 1.88) [18]. Induction of labor is likely associated with epidural use for several reasons.…”
Section: Discussionsupporting
confidence: 85%
“…A US-based study found similar, but not statistically significant, higher odds of epidural use associated with induction of labor (OR = 2.30, 95% CI 0.50 - 9.40) [9]. Further, an Australian study reported higher odds of epidural use among women with induced labor, similar to our report (OR = 1.86, 95% CI 1.83 - 1.88) [18]. Induction of labor is likely associated with epidural use for several reasons.…”
Section: Discussionsupporting
confidence: 85%
“…In units with 5000-7500 deliveries, only 3/8 (38%) units had such coverage. There were 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) labor rooms in each hospital. All units had computerized data collecting systems; however, only 9 units used this system to record complications.…”
Section: Resultsmentioning
confidence: 99%
“…8 In comparing obstetric anesthesia services within Israel with other developed countries, the overall use of labor epidural analgesia is higher. 3,9,10 A 1999 German survey reported a labor epidural analgesia rate less than 10%, with 10% of institutions not offering labor epidural analgesia. 11 Some European countries have reported high rates of labor epidural analgesia use, including 65% in Flanders, 12 and 61.6% in France, 13 with higher rates in teaching hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…R outinely collected population health datasets (PHDS) are an important data source for epidemiological and health services research, and they are frequently used to estimate prevalence of conditions, 1 examine temporal trends, [2][3][4] and evaluate health policy. 5,6 Data linkage allows enhanced utilization of PHDS for a range of research opportunities, including longitudinal studies, 7 the collection of outcome and cost data for randomized controlled trials, 8 and more recently the linkage of PHDS with laboratory data to find biomarkers of adverse outcomes.…”
mentioning
confidence: 99%